Analisis Beban Kerja Sumber Daya Manusia dalam Aktivitas Produksi Komoditi Sayuran Selada (Studi Kasus: CV Spirit Wira Utama) - Wildanur Adawiyah; Anggraini Sukmawati (Jurnal Manajemen dan Organisasi, 2013)
CV Spirit Wira Utama is a company that develops business model of agricultural (agribusiness) with hydroponic system without using greenhouse (open roof). The aims of this research are: (1) to  identify the Human Resources Development working description in producing lettuce, and (2) to  analyze the ideal number of employees based on employee workloads by counting Full Time Equivalent (FTE). Human Resources Development that supports in production process of lettuce commodity are divided  into the involved in off-farm and on-farm activities. The off farm activities includes technique, production, finance and marketing. Otherwise, on farm activity includes garden employees. The result of the research shows working time of Human Resource Development has not been optimal. Furthermore, to reach the effectiveness and efficiency an  alternative that can be carried out by a company is by combining the technique and production positions, job enlarging of finance and marketing positions, and improving the production phase of lettuce.Keywords: employee needs, FTE, hydroponic, lettuce, workload analysis